Comparative study of efficiency of disinfectants on human skin flora - CHAUDHARY A. A; DESAI U. R (International Journal of Pharma and Bio Sciences, 2018)
Bacteria are the major cause of infections and diseases in humans. It is assumed that the skin flora may be removed by simply washing the hands with soap and water. But it may be possible that some pathogenic resistant organisms remain intact to the skin and may cause disease to the host. So the first step in this study was to isolate the skin flora. Different colonies were observed even after disinfected fingers were touched on sterile Nutrient Agar medium. The same colonies present after disinfectionare taken into consideration. Mainly six different bacteria (one Gram positive cocci, two Gram negative encapsulated rods and three Gram positive rods) were isolated through this method and they were subjected to experimental disinfectants. The agar diffusion assay showed activity of disinfectants by means of inhibition zone. The results showed that compared to 3%Phenol, Dettol, Betadine and Lysol, 3%Savlon gave the best disinfectant activity against the isolated bacteria. So Savlon is considered as a better disinfectant.